Being a Jewish Writer Under the Romanian Fascist Regime: The Case of Mihail Sebastian - Paula Ganga (Slovo, 2012)
The rise of fascism in the late 1930s and 1940s in Romania had wide-ranging effects on the country’s Jewish minority. Among the affected categories, artists and writers had a special place as the presentation of their work was either restricted to solely within Jewish community or altogether forbidden. The case of the most representative Romanian Jewish writer of the time, Mihail Sebastian, and the way the anti-Semitic legislation in Romania the 1940s affected his work, is analyzed in the following article. Against the background of the evolution of the legal status of Jews in Romania from the 1930s until end World War II, Mihail Sebastian's biography will serve as an example of the odyssey Romanian artists and writers Jewish descent went through as their work became unacceptable to the fascist authorities. This article will mainly explore the situation of the Jewish artist in German-occupied Bucharest in 1944 by focusing on the process of writing and staging Sebastian's most popular play Steaua fără Nume (The Star without a Name). Click here to read full article